Impact of Quality on Ethics and Social Responsibility in Marketing, in Industries in Kerala in the present Indian Scenario - N.R.U.K. Kartha and V.P.Jagathy Raj (International Marketing Conference on Marketing & Society, 8-10 April, 2007, IIMK, 2007)
The paper `Impact of Quality on Ethics and Social Responsibility in Marketing in Industries in Kerala in the present Indian scenario' highlights the observations, based on a descriptive research carried out in five leading industries in Kerala, in the private and public sector. Ethics and social responsibilities, practiced in these industries, are reflected in the results of the survey conducted on specific queries like awareness of products/services provided by them, total understanding of the requirements of the customer, open discussion on technical matters, accountability of employees to the society and social needs, consumer ethics vis a vis business ethics etc. Team working goes a long way, in building relations, which in turn, results in a progressive and effective marketing strategy. This assumes paramount importance, considering the severe competition we are facing in the light of liberalization, privatization and globalization, which encompasses the globe. The prediction of India becoming a lead nation, along with USA, China and Japan, in this decade, can get fructified only if we follow a very high standards of ethics and social responsibility, in all domains including marketing. Organizations like TRW.Rane, Sundaram Fasteners, TVS Motors, in Chennai are a few among others in India, who have achieved the highest distinction in quality viz Deming Prize, and these demonstrate their commitment to quality, society and humanity at large. Cost effectiveness, without jeopardizing quality has become the need of the hour and MRTP has become history. This trait is being brought out through the survey and the results speak for themselves. Unethical practices like switch and bait, not only brings shame to the organization, and country but also results in the company getting wiped out from the market. Adherence to standards like ISO 14000 helps to maintain the minimum level of social responsibility and environmental friendliness. Like quality audit, safety audit etc, social audit is being insisted in all progressive countries to ensure that the organization comply with the minimum statutory requirements. The paper also touches upon Corporate Social Responsibility practiced in the industries and this becomes crystal clear through their commitment to improve the community. Green Marketing lays a lot of importance on the three Rs of environmentalism viz Reduce, Reuse and Recycle. The objective of any business is to achieve optimal profit and this is possible only by reducing the cost as well as waste. In this context, management tools like brainstorming, suggestion schemes, benchmarking etc becomes helpful. These characteristics are brought out through the analysis of survey results. The conclusions drawn throw a lot of information on the desirable practices with respect to Ethics and Social Responsibility in Marketing.